IMPLEMENTASI METODE MENGHAFAL AL QUR’AN DALAM MEWUJUDKAN KUALITAS HAFALAN AL QUR’AN (STUDI KOMPARASI DI PPTQ SAFINATUL HUDA III BANDUNG DIWEK DAN PPTQ NUR MUHAMMAD WONOAYU MOJOAGUNG) - Kamaliyatul Izzah Muqoddasah; Abdul Rouf; Dian Triana (Arsy : Jurnal Studi Islam, 2020)
The method of memorizing the Qur'an is an appropriate and fast way to enter information in the form of verses of the Qur'an, can save it and can also be delivered back outside the head. the quality of memorization of the Qur'an is a value that determines the good or bad memory of memorization of the Qur'an to a person as a whole, memorizing perfectly (ie memorizing the whole Qur'an by matching and perfecting his memorization), reading fluently and not making a mistake to the rules of reading in accordance with the correct recitation rules and always to persevere, routinize, devote all his energy and seriously in keeping memorization so as not to forget. This research was conducted at PPTQ Safinatul Huda III Bandung Diwek and PPTQ Nur Muhammad Wonoayu Mojoagung. This study focuses on the methods used by the two huts. Because both pesantren use the same method but differ in their application. This research is a comparative study to compare, know the advantages and disadvantages of the method of memorizing the Qur'an which is applied in both boarding schools to realize the quality of memorization.This study uses a qualitative method.The results of the research advantages and disadvantages is there is a time tarjet when to finish memorizing 30 juz.The results of research on the memorization of santri in PPTQ Nur Muhammad Wonoayu Mojoagung are seen from the interview data, examining santri and alumni shows that it can be said to produce good quality, and will be better if memorization in muroja'ah is istiqomah and patiently. The results of the research advantages and disadvantages is there is a time tarjet when to finish memorizing 30 juz